Effects of carbon sources on electrochemical performance of Li4Ti5O12/C composite anode materials - Liu, Ping; Zhang, Zhi-an; Li, Jie; Lai, Yan-qing (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2010)
Li 4 Ti 5 O 12 /C composite materials were synthesized by two-step solid state reaction method with glucose, sucrose, and starch as carbon sources, respectively. The effects of carbon sources on the structure, morphology, and electrochemical performance of Li 4 Ti 5 O 12 /C composite materials were investigated by SEM, XRD and electrochemical tests. The results indicate that carbon sources have almost no effect on the structure of Li 4 Ti 5 O 12 /C composite materials. The initial discharge capacities of the Li 4 Ti 5 O 12 /C composite materials are slightly lower than those of as-synthesized Li 4 Ti 5 O 12 . However, Li 4 Ti 5 O 12 /C composite materials show better electrochemical rate performance than the as-synthesized Li 4 Ti 5 O 12 . The capacity retention (79%) of the Li 4 Ti 5 O 12 /C composite materials with starch as carbon source, is higher than that of Li 4 Ti 5 O 12 /C composite materials with glucose and sucrose as carbon source at current rate of 2.0 C .